Súmula vinculante e o instituto dos assentos: seu sentido normativo e o problema da liberdade judicial - Miranda dos Santos, Luiz Elias (2014)
Given the circumstances of the relevant role of jurisdiction today (given that it cannot simply be understood based on the idea of ​​classification of the legal precept to the case), one cannot ignore anymore the creative sense that it has, both towards solving the problems that emerge from the dynamic community for densification of dogmatic or to the very development of the law beyond the purely positivist conception of it. In this scenario, as the flip side of the creative activity of the judges, there is the situation of abuse that freedom by the judges as excess in creationism by the agents of the jurisdiction. In Brazil, the problems of freedom loomed up the overwhelming at all levels of the judiciary caused by intense legalization of the Brazilian society, encouraging the creation of binding precedents. As a way to offer a strong objection to the institution of the binding precedent, the present study is an analysis of the same (with the aid of the methodology compared to the movement of ideas) comparing it with the former Portuguese Institute of seats in order to show the impropriety of binding precedents that promote a relative decrease of the processes, causing other disorders such as assigning legislation characters to the Supreme Court, and a breakdown of the principle of separation of powers.